1999
DOI: 10.3138/cmlr.55.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of the French in French Immersion: Concept Development in Early FI

Abstract: This article investigates children's concept development and use of exploratory talk in the primary years of early French immersion (K-3). The authors relate data from a case study of a primary program to personal teaching experience and research in language and learning and developmental psychology. They then suggest some possible approaches to enhancing concept development and exploratory talk in that particular learning setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In fact, while first language use has long been a topic of much debate and controversy in many second and foreign language contexts beyond French immersion (e.g., Cook, 2001; Levine, 2003; Liebscher & Dailey‐O’Cain, 2004; Macaro, 2005, 2009; McMillan & Turnbull, 2009; Turnbull, 2001) the results of this debate have generally been ignored by French immersion professional organizations and policy makers throughout Canada. Nevertheless, some researchers (e.g., Behan, Turnbull, & Spek, 1997; McMillan & Turnbull, 2009; Sanaoui, 2005, 2007; Skerritt, 2003; Swain & Lapkin, 2000; Walsh & Yeoman, 1999) suggested that teacher and learner codeswitching (CS) practice varies significantly in French immersion, especially in teaching and learning content. All scholars call for more research on CS in French immersion.…”
mentioning
confidence: 99%
“…In fact, while first language use has long been a topic of much debate and controversy in many second and foreign language contexts beyond French immersion (e.g., Cook, 2001; Levine, 2003; Liebscher & Dailey‐O’Cain, 2004; Macaro, 2005, 2009; McMillan & Turnbull, 2009; Turnbull, 2001) the results of this debate have generally been ignored by French immersion professional organizations and policy makers throughout Canada. Nevertheless, some researchers (e.g., Behan, Turnbull, & Spek, 1997; McMillan & Turnbull, 2009; Sanaoui, 2005, 2007; Skerritt, 2003; Swain & Lapkin, 2000; Walsh & Yeoman, 1999) suggested that teacher and learner codeswitching (CS) practice varies significantly in French immersion, especially in teaching and learning content. All scholars call for more research on CS in French immersion.…”
mentioning
confidence: 99%
“…Some research has, for example, considered how children's conceptual development is affected, not always positively as it turns out, by French immersion teaching. Such teaching has been found to be restrictive with over-reliance on closed questions from teachers concentrating on concrete vocabulary in the early years of a programme (Walsh and Yeoman, 1999). The author of another detailed study of 215 grade 6 learners in Montreal, concluded that mere exposure to a second language, even when that exposure is intensive and sustained, is not enough to ensure an increase in learners' grammatical knowledge and hence their ability to generate language (Morris, 2001).…”
mentioning
confidence: 99%